Controlled intramolecular H-transfer in malonaldehyde in the electronic ground state mediated through the conical intersection of 1nπ* and 1ππ* excited electronic states. Issue 36 (3rd September 2019) - Nandipati, K. R.; Kanakati, Arun Kumar; Singh, H.; Mahapatra, S.
Abstract : We report photo-isomerization of malonaldehyde in its electronic ground state (S0 ), mediated by coupled 1 nπ*(S1 )– 1 ππ*(S2 ) excited electronic states, accomplished with the aid of optimally designed ultraviolet (UV)-laser pulses. Abstract : We report photo-isomerization of malonaldehyde in its electronic ground state (S0 ), mediated by coupled 1 nπ*(S1 )– 1 ππ*(S2 ) excited electronic states, accomplished with the aid of optimally designed ultraviolet (UV)-laser pulses. In particular, control of H-transfer from a configuration predominantly located in the left well (say, reactant) to that in the right well (say, product) of the electronic ground S0 potential energy surface is achieved by a pump–dump mechanism including the nonadiabatic interactions between the excited S1 and S2 states. An interplay between the nonadiabatic coupling due to the conical intersection of the S1 and S2 states and the laser–molecule interaction is found to be imprinted in the time-dependent electronic population. The latter is also examined by employing optimal fields of varying intensities and frequencies of the UV laser pulses. For the purpose of the present study, we constructed a three-state and two-mode coupled diabatic Hamiltonian with the help of adiabatic electronic energies and transition dipole moments calculated by ab initio quantum chemistry methods. The electronic diabatic model is developed using the calculated adiabatic energies of the two excited electronic states (S1 and S2 ) in order to carry out the dynamics study. The optimal fields for achieving the controlled isomerization are designed within the framework of optimal control theory employing the optimization technique of a multitarget functional using the genetic algorithm. The laser-driven dynamics of the system is treated by numerically solving the time-dependent Schrödinger equation within the dipole approximation. A time-averaged yield of the target product of ∼40% is achieved in the present treatment of dynamics with optimal laser pulses.